Effect of treatment with carteolol and latanoprost in newly diagnosed primary open-angle glaucoma on peripapillary vessel density - Lestak, Jan; Fus, Martin; Pitrova, Sarka (Biomedical papers, 2024)
Background and Aim. In a previous follow-up of glaucoma patients taking carteolol or latanoprost, we found a greater progression of visual field changes with the prostaglandin than the betablocker. In the present study we compared the impact of carteolol and latanoprost on peripapillary vessel density in newly diagnosed primary open-angle glaucoma (POAG) patients. Methods. The study consisted of two groups of POAG patients. There were 46 patient eyes treated with carteolol (Carteol LP 2%) in the first group and 52 eyes treated with latanoprost (Xalatan 0.005%) in the second. Intraocular pressure (IOP), vessel density (VD) and visual field were assessed in all patients. VD was measured peripapillary by optical coherence tomography angiography (OCTA) with the Avanti RTVue XR in eight segments: Inferior Temporal - IT (1); Temporal Inferior -TI (2); Temporal Superior - TS (3); Superior Temporal - ST (4); Superior Nasal - SN (5); Nasal Superior - NS (6); Nasal Inferior - NI (7) and Inferior Nasal - IN (8). The measurements were compared before and after three months of treatment. The visual field was examined with a fast threshold glaucoma program using a Medmont M 700 instrument from Medmont International Pty Ltd. and only when a diagnosis of POAG was done. The overall defect (OD) was assessed. Results. Before treatment, there was no difference between groups in either OD or VD. After treatment, there was a decrease in IOP in both groups. In the carteolol-treated group, the mean decrease was 5.8 mmHg and in the latanoprost-treated eyes, the mean decrease was 7 mmHg. The difference was not statistically significant (P=0.133). After treatment with carteolol, there was a statistically significant increase in VD in segments 4, 5 and 6. After latanoprost treatment, VD was statistically significantly improved only in segment 5. A greater increase in VD values was found in eyes treated with carteolol than in eyes treated with latanoprost. Conclusion. Carteolol had a better effect on vessel density than latanoprost.
Keywords: primary open-angle glaucoma; peripapillary vessel density; treatment with carteolol and latanoprost.